PERANCANGAN LOGO BRAND IDENTITAS OBJEK WISATA TUKAD BARONG SEBAGAI UPAYA BRANDING DAN PENGGUNAAN INSTAGRAM SEBAGAI MEDIA PROMOSI - Anak Agung Istri Agung Maheswari; Maria Jesika Nadia Bugis bugis (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Tukad Barong Tourist Attraction is one of the icons of tourist attractions owned by Yangapi Village. The location of Tukad Barong is located in Banjar Umbalan and is managed by POKDARWIS under the auspices of BUMDES. This waterfall is one of the attractive places for the surrounding community with a root bridge and waterfall is perfect for travelers who want to capture their small moments through the camera they have. The program that I will do is Logo Making and Using Instagram as a Promotional Medium for Tukad Barong Tourist Attractions. The purpose of holding this work program activity is to help POKDARWIS in promoting the Tukad Barong tourist attraction which was vacuumed due to the Covid-19 Pandemic and create branding in the form of a logo for the Tukad Barong Tourism Object. Alasn the use of Instagram as a promotional medium because Instagram is one of the social media whose users are quite high, so it is hoped that the use of Instagram as a medium for Promotion of Tukad Barong Tourism Objects itself has a good impact on Tukad Barong Tourism Objects in the future. Keywords: Logo, Attractions, Instagram, POKDARWIS, Promotion, Tukad Barong